*Changes in the seroepidemiological pattern of Helicobacter pylori infection over the last 10 years in Turkey - Ali ÖZDEN; Gülendam BOZDAYI; Muhip ÖZKAN; S.Kenan KÖSE (Turkish Journal of Gastroenterology, 2019)
-